Bitcoin Between The Economy and Islamic Law - Aicha Larfi (Sekolah Tinggi Ilmu Bahasa Arab Darul Ulum Banyuanyar Pamekasan, 2022)
From the womb of cyberspace bitcoin, the first decentralized digital currency, differed from the traditional currencies that we used to revolutionize the world of finance, and in light of its rapid spread, became a source of concern and question about the impact of this child on the economy of states and individuals, opinions differed around him between supporters and opponents, hence this study came in order to search and extrapolate this currency to know the positions of countries and major companies and what economists expected for their future, and the legitimate vision is not yet clear, and it became a duty Intensified efforts to diagnose and adapt this contemporary event and thereby indicate its judgment and controls.